Changes in forest areas and land cover and their causes using intensity analysis: the case of Alabarda forest planning unit - Kaptan, Sinan; Kaptan, Sinan (Springer, 2021)
The examination of land cover change, as the main driving force of global climate change, and the determination of its economic, ecological, and social effects are necessary for making the right decisions in sustainable development, planning, and management. This study, conducted in the local forest areas of Alabarda, located in Tavsanli District (Turkey), examined temporal and spatial changes in land cover using an intensity analysis consisting of three levels: interval, category, and transition. Using the three maps of 1994, 2004, and 2015, we analyzed the land use changes during two time intervals (1993-2004 and 2004-2015) in the area for six categories, including three for forest areas (Productive, Degraded, and Treeless) and three for non-forest areas (Others, e.g., mine sites, roads, wetlands; Settlement; and Cultivated). The interval level results of the analysis showed that the land change rate was more rapid in the 2004-2015 time interval compared to 1993-2004. According to the category level results, in both time intervals, the Productive category was dormant in terms of loss and gain, whereas the Cultivated category was active. The level showing transitions between categories indicated that the Productive category targeted the Treeless and Cultivated losses in the first time interval and targeted the Degraded losses most intensely in the second time interval. The successful forestry activities (afforestation and rehabilitation) carried out by the government as of 2006 and the ongoing migration of the population from the region have had a joint effect on the increase of forest areas and the transformation of Degraded forest areas into Productive ones in the study area.
Keywords: Intensity Analysis; Land Transformation; Forest Cover Change; Systematic Transition; Gis; Turkey